Recent Changes - Search:

Research


edit SideBar


MimeTexTest

{$ x^2 + y^3 = z^4 $}


{$\array{CCC$\Large f=b_\0+\frac{a_\1}{b_\1+\frac{a_2}{b_2+\frac{a_3}{b_3+a_4}}} & \hspace{10} {\small\rm{Notes and\atop mimeTeX Sandbox}} \hspace{10} } \Large \scrJ^{ij}=\frac12\vareps_{ijk}\[\array{cc$\sig_k&0\\0&\sig_k}\] $}


{$\large \Bigint\limits_^{-1$\infty} e^{-x^2} dx\ =\ \frac{\sqrt\pi}2$}

{$\frac{-b\pm\sqrt{b^2-4ac}}{2a}$}

{$ 1+\frac{1+\frac{1+\frac{a}{b}}{c}}{d} $}

{$e^{i \pi}-1=-2 $}, {$e^{i\pi}+1=0$}

{$ sqrt{n} $} A{$\vee$}B


{$ \Large\Bigint_{} e^x = \LARGE f \Large(u_n) $}

{$S = S_{0} e^{\frac{-TE}{T_{2}^{*}}} $}


{$X \oplus S = \left\{ x+y | x \in X, y \in S \right\}$}


{$\frac{number\ of\ favorable\ outcomes}{total\ number\ of\ possible\ outcomes} = \frac{m}{n}$}

{$\frac{\sqrt{2}}{\sqrt{2}}$}

{$\mathbb{R}^n$}


{$ \Large \mathbf{F} = - \left( \frac{\partial U}{\partial x} \hat{\mathbf{i}} + \frac{\partial U}{\partial y}\hat{\mathbf{j}} + \frac{\partial U}{\partial z}\hat{\mathbf{k}} \right) = - \nabla U $}


{$ a \in \mathbb{N} \wedge b \in \mathbb{N}$}


{$\frac{\sqrt{25}}{\sqrt{12}}$}


{$\Psi=\frac{CO_2}{CaCO_3$}}


Edit - History - Print - Recent Changes - Search
Page last modified on October 23, 2006, at 05:49 PM EST